Comparison of Therapy Effects Between A Single Non-Steroidal Anti-Inflammatory Drug and The Combination with Muscle Relaxant on The Degree of Lower Back Pain - Santo Fitriantoro; Betty Soedaly (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Lower back pain often results from poor ergonomic practice, characterized by localized discomfort between the costal border and lower gluteus folds, lasting more than one day. Possible factors contributing to this condition include age, gender, body mass index, ergonomics, load, work life, smoking habits, physical activity, or sports habits. Objective: This study aimed to examine the difference in therapy effects between a single non-steroidal anti-inflammatory drug (NSAID) (sodium diclofenac) and the combination of muscle relaxants (diazepam) against the severity of lower back pain. The degree of pain was assessed using the Alternative Method of Quantitative Pain Assessment (MAPKN) at HM Ryacudu Hospital, North Lampung. The sample consisted of 40 patients receiving medications at the Neurology Polyclinic. Methods: A quantitative method was used with a descriptive comparative approach. Results: The results showed that statistical analysis obtained a significance level of 0.737, indicating a normal data distribution. A paired sample t-test had a significance level of 0.000, which suggested a rejection of Ho and an acceptance of Ha. Conclusion: Based on the results, the combination therapy of NSAID (sodium diclofenac) and muscle relaxant (diazepam) was more effective in reducing lower back pain than using only an anti-inflammatory drug.